Landasan Pengadaan Tanah Untuk Kepentingan Umum Bagi Pembangunan - Mohammad Roesli; M Hidayat (ILIN Institute, 2022)
The research objective to analyze the basic reasons for the state to control the earth, water and natural resources contained therein. This research is a normative research. The results of this study are the basis for land acquisition for the public interest based on several aspects, namely the ontological aspect (teachings on essence), axiological (teachings on values), epistemological aspects (teachings on knowledge), and teleological aspects (teachings on goals). Everything must be in accordance with the 1945 Constitution of the Republic of Indonesia and set forth in Law Number 2 of 2012 is land acquisition for development in the public interest aimed at realizing a just, prosperous and prosperous society. The government needs to carry out development, to ensure the implementation of development for the public interest, land is needed whose procurement is carried out by prioritizing the principles of humanity, democracy and justice, carried out based on the principles of: humanity, justice, benefit, certainty, openness, agreement, participation, welfare, sustainability, and alignment. The implication is that the principle of law is an ideal element of law. Tujuan penelitian menganalisis alasan mendasar terhadap bumi, air dan kekayaan alam yang terkandung di dalamnya itu harus dikuasai oleh negara. Penelitian ini merupakan penelitian yang bersifat normative. Hasil penelitian ini adalah landasan pengadaan tanah untuk kepentingan umum dilakukan berdasarkan dari beberapa aspek, yaitu aspek ontologis (ajaran tentang hakekat), aksiologis (ajaran tentang nilai), aspek epistemologis (ajaran tentang pengetahuan), dan aspek teleologis (ajaran tentang tujuan). Kesemuanya harus sesuai dengan Undang-undang Dasar Negara Republik Indonesia 1945 dan dituangkan dalam Undang-undang Nomer 2 tahun 2012 adalah pengadaan tanah bagi pembangunan untuk kepentingan umum bertujuan mewujudkan masyarakat yang adil, makmur, dan sejahtera. Pemerintah perlu melaksanakan pembangunan, untuk menjamin terselenggaranya pembangunan untuk kepentingan umum, diperlukan tanah yang pengadaannya dilaksanakan dengan mengedepankan prinsip kemanusiaan, demokratis, dan adil, dilaksanakan berdasarkan asas: kemanusiaan, keadilan, kemanfaatan, kepastian, keterbukaan, kesepakatan, keikutsertaan, kesejahteraan, keberlanjutan, dan keselarasan. Implikasinya pada asas hukum merupakan unsur ideal dari hukum.